Between Tun Mustapha and the deep blue sea: the political ecology of blue carbon in Sabah. Issue 55 (January 2016) - Thomas, Sebastian
Graphical abstract: Highlights: Blue carbon resources provide extensive climate, cultural, and livelihood benefits. Project opportunities are constrained by socially and politically charged situations. This paper applies a novel systems-based political ecology approach to sustainability science. History, race, religion, gender, and politics are critical to effective blue carbon project development. Abstract: Coastal 'blue carbon' ecosystem resources are rich carbon stores, offer extensive benefits beyond carbon sequestration, and are marginalized in global markets and policy mechanisms. The participation of blue carbon project activities in international market frameworks is limited by a dearth of appropriate research across disciplinary boundaries, particularly in terms of the cultural and political dynamics that affect project implementation. The socially and politically charged contexts of many developing countries constrain project opportunities, and understanding specific local governance dynamics is therefore of critical importance to policy makers, development practitioners, and the private sector. This paper applies a systems-based political ecology research and analytical approach to explore the social and political dynamics affecting the potential development of blue carbon projects in a proposed marine reserve in Sabah, Malaysia. The investigative focus is situated in its historical context, described and mapped as an influence system in collaboration with local experts, with the elements of that system then explored in detail, through a workshop, survey, and interviews with a diverse range of local stakeholders. Key findings include that historical realities play a vital role in present relationships; effective governance is likely to require international collaboration to minimize inequity and corruption; race and religion continue to be used as tools of political imperialism; and dominant actors in Sabah would be well advised to recognize the growing, informed cohesion of Sabahan society, and its drive for equitable, ecologically sustainable development. The paper contributes a novel methodological approach to sustainability science research, provides unique data on a case study area relevant to climate change policy, and identifies important leverage points for the development of blue carbon finance and policy instruments in South-East Asia and beyond.